Tailoring the continuum of care for substance use problems to persons with an Islamic migration background: a co-creative case study - Pouille, Aline; Bouachiba, Arafat; De Ruysscher, Clara; Vander Laenen, Freya; Vanderplasschen, Wouter (Frontiers in Psychiatry, 2023)
Structural inequity and stigma impose barriers towards substance use prevention and recovery support for persons with an Islamic migration background in non-Islamic majority countries. Similar issues of differential power often keep them silenced in research. Therefore, we explore the continuum of care for substance use problems regarding persons with an Islamic migration background, drawing from a co-creative case study with Arafat, whose lived and professional experiences as a Muslim with a history of problem substance working in the field, were blended with academic literature through the process of 'plugging in'. We discuss (1) culturally competent and selective substance use prevention, (2) facilitating access to adequate support services, (3) culturally competent substance use treatment and (4) supporting long-term recovery for persons with an Islamic background from a combined academic, professional and lived experiences perspective. We discuss the need for tailored interventions that are able to overcome structural inequities and address ethnocultural sensitivities, needs and strengths. Intermediary community organizations, cultural competence of treatment and recovery-oriented systems of care may bridge the gaps between what is needed and what is available. However, it is important to be conscious that hands-on solutions at the personal level do not absolve the responsibility of searching for systemic solutions. Furthermore, awareness of the fine line between cultural competence and culturalization, taking into account the danger of essentializing, othering and overlooking other intersectional traits of diversity, is needed.